The Effect of Work Motivation and Work Environment on Performance with Work Supervision as Intervenning Variables in the Office Medan Region II Airport Authority - Albert Agung Soelistyono; Wilchan Robain (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The purpose of this study was to determine the effect of work motivation and work environment on performance with work supervision as an intervening variable. This research was conducted at the Regional Airport Authority Office, Medan. saturated sample technique, the type of research used is associative quantitative. The research model used is path analysis and research data collection was carried out by distributing questionnaires and surveys. Based on the results of the research that has been done and data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Work environment has a positive and significant effect on performance as evidenced by the original sample value of 0.744 and p values of 0.000 <0.05. Environment Work has a positive and significant effect on Supervision with an Original sample value of 0.329 with a p value of 0.001 <0.05. Work motivation has a positive and significant effect on performance with an original sample value of -0.153 with a p-value of 0.044 <0.05. Work Motivation has a positive and significant effect Control over the original sample 0.286 P values 0.046. Oversight has a negative and not significant effect on the original sample -0.011 P value 0.904. The indirect effect of the work environment on performance through supervision is negative and not significant. Original sample -0.004 P values 0.909. The indirect effect of work motivation on performance through supervision is negative and not significant. Work motivation has a positive and significant effect on performance with an original sample value of -0.153 with a p-value of 0.044 <0.05. Work Motivation has a positive and significant effect Control over the original sample 0.286 P values 0.046. Oversight has a negative and not significant effect on the original sample -0.011 P value 0.904. The indirect effect of the work environment on performance through supervision is negative and not significant. Original sample -0.004 P values 0.909. The indirect effect of work motivation on performance through supervision is negative and not significant. Work motivation has a positive and significant effect on performance with an original sample value of -0.153 with a p-value of 0.044 <0.05. Work Motivation has a positive and significant effect Control over the original sample 0.286 P values 0.046. Oversight has a negative and not significant effect on the original sample -0.011 P value 0.904. The indirect effect of the work environment on performance through supervision is negative and not significant. Original sample -0.004 P values 0.909. The indirect effect of work motivation on performance through supervision is negative and not significant. Oversight has a negative and not significant effect on the original sample -0.011 P value 0.904. The indirect effect of the work environment on performance through supervision is negative and not significant. Original sample -0.004 P values 0.909. The indirect effect of work motivation on performance through supervision is negative and not significant. Oversight has a negative and not significant effect on the original sample -0.011 P value 0.904. The indirect effect of the work environment on performance through supervision is negative and not significant. Original sample -0.004 P values 0.909. The indirect effect of work motivation on performance through supervision is negative and not significant.